Medical Imaging in Guyana, development and status - Chanderballi , Ramona (Radiography Open, 2019)
Medical imaging services have been rapidly advancing in Guyana over the last decade. It is time to look back, and state the todays’ situation. With a population, under 1 million, Guyana, according to the World Factbook (1), is the third smallest country in South America. Guyana was originally a Dutch colony in the 17th century, by 1815 had become a British possession. The abolition of slavery led to settlement of urban areas by former slaves and the importation of indentured servants from India to work the sugar plantations. Tropical rainforests cover over 80 percent, and its agricultural lands are fertile. A resulting ethno-cultural divide has persisted and has led to turbulent politics. Guyana achieved independence from the UK in 1966. In 1992, the country is first free and fair election since independence. The economy is growing; still at a high unemployment. According to the World Factbook, it is (per 2018) a young population; mean age for both females and males are 28 years, and life expectancy 68y. Compared with other neighboring countries, Guyana ranks poorly concerning basic health indicators (2), basic health services in the interior are primitive to non-existent.